Determinants of Tuberculosis Disease in the Coastal Area of Kulisusu Sub District, Indonesia - Saparina L, Titi; Akbar , Muhammad Ikhsan; Tasnim, Tasnim; Mulyani, Sri; Noviati, Noviati (Public Health of Indonesia, 2024)
Background:Tuberculosis (TB) continues to be a significant public health issue in the coastal area of Kulisusu Sub-District, North Buton Regency, Indonesia. The prevalence of TB in this region has been increasing steadily, with 294 reported cases in 2023, compared to 281 cases in 2022. As an infectious disease, tuberculosis requires effective control strategies, which necessitate identifying its key determinants. Objective:This study aims to identify the risk factors associated with tuberculosis in Kulisusu Sub-District, North Buton Regency, Southeast Sulawesi Province, Indonesia. Methods:This quantitative research employed a case-control study design. The study population consisted of 172 individuals, with a sample of 25 cases and 25 controls, selected through proportional random sampling and age matching. Data analysis was conducted using univariate and bivariate analysis, with statistical significance tested using the Odds Ratio (OR). Results:The Odds Ratio (OR) analysis revealed the following risk factors for tuberculosis: knowledge (OR = 11.156), income (OR = 4.333), smoking habits (OR = 8.500), and residential density (OR = 5.630). These findings indicate that poor knowledge, low income, smoking habits, and high residential density are significant risk factors for tuberculosis in the Kulisusu Sub-District. Conclusion:The key determinants of tuberculosis in Kulisusu Sub-District include knowledge, income, smoking habits, and residential density. Health promotion strategies aimed at reducing TB prevalence should focus on these factors, with comprehensive and sustainable approaches to prevention. Keywords:knowledge; income; smoking habits; residential density; tuberculosis; Indonesia